Near-infrared Fourier transform surface-enhanced Raman scattering spectroscopy of 1,4-benzodiazepine drugs employing gold films over nanospheres - Schneider, Siegfried; Hennemann, Matthias; Clark, Timothy; et al. (Journal of Raman Spectroscopy, 2004)
SERS spectra of eight benzodiazepine drugs were recorded with an FT-NIR Raman spectrometer employing AuFONs (gold films over nanospheres) as SERS-active substrates. A tentative assignment of the vibrational bands was made by comparison with the Raman spectra of crystalline reference samples and the results of density functional theory (DFT) calculations. It is concluded that the bands observed in the SERS spectra are almost exclusively due to vibrations located on rings a and b of the benzodiazepine moiety. The latter should be adsorbed with the molecular plane essentially orthogonal to the metal surface. However, different adsorption geometries are postulated for derivatives containing NH or NCH3 groups. It is demonstrated that a few hundred nanograms of analyte per well are sufficient to record spectra that allow identification and discrimination of the drugs. Such amounts can be collected at the output of an HPLC instrument employed for separating these drugs from blood serum. Copyright (C) 2004 John Wiley Sons, Ltd.
Keywords: surface-enhanced Raman scattering; gold films over nanospheres; benzodiazepine drugs; high-performance liquid chromatography; high-throughput analysis